Diversity of several estimates transformed on time scales - Sahir, Muhammad Jibril Shahab; Afzal, Deeba; İnç, Mustafa; Alshomrani, Ali Saleh (Springer, 2023)
In this research article, we prove several generalizations of reverse Callebaut, Rogers-Holder, and Cauchy-Schwarz inequalities via reverses of Young inequalities on time scales. Discrete, continuous, and quantum versions of the results are unified and extended on time scales.
Keywords: Time scales; Specht ratio; Reverses of Callebaut; Rogers-Holder; Cauchy-Schwarz inequalities